Exclusive diffractive production of π+π-π+π- via the intermediate [sigma][sigma] and [rho][rho] states in proton-proton collisions within tensor Pomeron - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2016)
We present first predictions of the cross sections and differential distributions for the central exclusive reaction pp→ppπ+π−π+π− being studied at RHIC and LHC. The amplitudes for the processes are formulated in terms of the tensor Pomeron and tensor f2R Reggeon exchanges with the vertices respecting the standard crossing and charge-conjugation relations of quantum field theory. The σσ and ρρ contributions to the π+π−π+π− final state are considered, focusing on their specificities. The correct inclusion of the Pomeron spin structure seems crucial for the considered sequential mechanisms, in particular for the ρρ contribution which is treated here for the first time. The mechanism considered gives a significant contribution to the pp→ppπ+π−π+π− reaction. We adjust parameters of our model to the CERN-ISR experimental data and present several predictions for the STAR, ALICE, ATLAS, and CMS experiments. A measurable cross section of order of a few μb is obtained, including the experimental cuts relevant for the LHC experiments. We show the influence of the experimental cuts on the integrated cross section and on various differential distributions.
Im Titel sind "sigma" und "rho" als griechische Buchstaben dargestellt
Im Titel sind die Zeichen "+" und "-" hochgestellt
Gesehen am 16.06.2020